Human prion diseases. Issue 3 (June 2019) - Wang, Han; Rhoads, Daniel D.; Appleby, Brian S.
Abstract : Purpose of review: Prion diseases are rapidly progressive neurodegenerative conditions that can be difficult to diagnose and are transmissible under specific circumstances. The authors will provide background regarding prion disease and focus on diagnostic tools. Recent findings: Prion disease is caused by misfolded prion protein. The three possible causes of prion disease include sporadic (85%), genetic (10–15%), and acquired (<1%). Acquired prion diseases include kuru, iatrogenic, and variant Creutzfeldt–Jakob disease. Prion diseases differ in their clinical manifestation, neuropathology, and diagnostic test results. A variety of recent diagnostic tools have evolved that allow more reliable antemortem diagnosis of prion disease such as brain MRI and cerebrospinal fluid real-time quaking-induced conversion. Special infectivity guidelines must be followed when dealing with central nervous system tissue, but only standard precautions are needed for routine clinical care of patients with prion disease. Summary: The only way to definitely diagnose prion disease and determine its type is via neuropathologic examination. However, brain MRI and cerebrospinal fluid real-time quaking-induced conversion have drastically increased diagnostic accuracy and are important tests to use when evaluating patients with suspected prion disease.